Domain structure and in-plane switching in a highly strained Bi0.9Sm0.1FeO3 film - Yang, Yurong (2014)
We report the domain structure and ferroelectric properties of a 32 nm-thick Bi0.9Sm0.1FeO3film epitaxially grown on a LaAlO3 (LAO) substrate. This film exhibits a monoclinic Mc phase, with its monoclinic distortion and anisotropy of in-plane (IP) lattice parameters being both smaller than those of pure BiFeO3 (BFO) grown on LaAlO3. Polarization hysteresis loops measured using a quasi-planar capacitor show an in-planepolarization up to 30 μC/cm2. Piezoresponse force microcopy demonstrates that a 180° in-planepolarization switching accompanied by a 90° domain wall rotation takes place after electric poling. First-principles calculations suggest the differences between highly strained Sm-substituted and pure BiFeO3.